Diquat-induced oxidative stress increases intestinal permeability, impairs mitochondrial function, and triggers mitophagy in piglets. (17th March 2018) - Cao, Shuting; Wu, Huan; Wang, ChunChun; Zhang, Qianhui; Jiao, Lefei; Lin, Fanghui; Hu, Caihong H
Abstract: In the present study, we investigated the influence of diquat-induced oxidative stress on intestinal barrier, mitochondrial function, and the level of mitophagy in piglets. Twelve male Duroc × Landrace × Yorkshire 35-d-old pigs (weaned at 21 d of age), with an average body of 9.6 kg, were allotted to two treatments of six piglets each including the challenged group and the control group. The challenged pigs were injected with 100 mg/kg bodyweight diquat and control pigs injected with 0.9% (w/v) NaCl solution. The results showed that diquat injection decreased ADFI and ADG. Diquat decreased ( P < 0.05) the activities of superoxide dismutase and glutathione peroxidase and increased ( P < 0.05) the malondialdehyde concentrations. The lower ( P < 0.05) transepithelial electrical resistance and higher ( P < 0.05) paracellular permeability of fluorescein isothiocyanatedextran 4 kDa were found in diquat challenged piglets. Meanwhile, diquat decreased ( P < 0.05) the protein abundance of claudin-1, occluding, and zonula occludens-1 in jejunum compared with the control group. Diquat-induced mitochondrial dysfunction, as demonstrated by increased ( P < 0.05) reactive oxygen species production and decreased ( P < 0.05) membrane potential of intestinal mitochondria. Diquat-injected pigs revealed a decrease ( P < 0.05) of mRNA abundance of genes related to mitochondrial biogenesis and functions, PPARg coactivator-1α, mammalian-silencing information regulator-1, nuclear respiratory factor-1, mt transcription factor A, mt single-strand DNA-binding protein, mt polymerase r, glucokinase, citrate synthase, ATP synthase, and cytochrome coxidase subunit I and V in the jejunum. Diquat induced an increase ( P < 0.05) in expression of mitophagy-related proteins, phosphatase and tensin homologue deleted on chromosome 10-induced putative kinase, and Parkin in the intestinal mitochondria, as well as an enhancement of the ratio of light chain 3-II (LC3 -II) to LC3-I content in the jejunal mucosa. These results suggest that oxidative stress disrupted the intestinal barrier, caused mitochondrial dysfunction, and triggered mitophagy.